The Twisted Claw - Dixon Franklin W.; Franklin W. Dixon (Canada Franklin W. Dixon, 1939)
follows Frank and Joe Hardy as they investigate a series of museum thefts involving ancient pirate treasure.
Keywords: refers primarily to the 18th volume in the Hardy Boys Mystery Stories series by Franklin W. Dixon; focuses on the dangers of greed, impulsiveness, and disrespecting the wisdom of elders